Sacubitril/valsartan is associated with improvements in quality of life in adult congenital heart disease patients with systemic right ventricular failure - Philippine Kiès; Marieke Nederend; Ralph M.L. Neijenhuis; Anna E. van Groningen; Monique R.M. Jongbloed; Hubert W. Vliegen; J. Wouter Jukema; Anastasia D. Egorova (Open Heart)
Background Short-term improvements in quality of life (QOL) have been reported in adult congenital heart disease patients with systemic right ventricle (sRV) failure after treatment with sacubitril/valsartan. This study aimed to evaluate the medium-term QOL changes in sRV failure patients treated with sacubitril/valsartan.Methods In this single-centre, prospective cohort study, patients with symptomatic sRV failure completed the Netherlands Organisation for Applied Scientific Research/Academic Hospital Leiden Questionnaire for Adult’s Health-Related Quality of Life (TAAQOL) at baseline and after starting treatment with sacubitril/valsartan. The TAAQOL was taken at structured outpatient follow-up moments after 6, 12, 24 and 36 months of treatment. Linear mixed effects models were used to evaluate the medium-term changes in 12 QOL domains.Results Of 40 sRV failure patients initiated on sacubitril/valsartan, 35 completed the titration phase, and 31 filled in a total of 98 TAAQOL questionnaires (response rate 77.5%). Significant improvements in gross motoric functioning (p=0.008), cognitive function (p=0.002), sleep (p=0.041), social functioning (p<0.001) and daily activities (p=0.001) were observed during follow-up. No significant changes were observed in fine motoric functioning, pain, sexuality, vitality, positive, depressive or aggressive emotions. Of interest, periods with restrictions relating to the COVID-19 pandemic did not significantly influence changes over time in any of the 12 QOL domains.Conclusions Sacubitril/valsartan treatment was associated with persistent medium-term QOL improvements in gross motoric functioning, cognitive function, sleep, social functioning and daily activities domains in sRV failure patients. Self-perceived QOL of sRV failure patients may be amenable to improvement with sacubitril/valsartan.